To find which expression equals \( A = 5 - \frac{11}{3} \), we first need to simplify \( 5 - \frac{11}{3} \).
-
Convert \( 5 \) into a fraction that has the same denominator as \( \frac{11}{3} \): \[ 5 = \frac{15}{3} \]
-
Now perform the subtraction: \[ A = \frac{15}{3} - \frac{11}{3} = \frac{15 - 11}{3} = \frac{4}{3} \]
Now that we know \( A = \frac{4}{3} \) (which can also be expressed as \( 1 \frac{1}{3} \) or \( 1.33 \)), we need to evaluate each expression given in the options and see which one equals \( \frac{4}{3} \).
A. \( A = 1 \frac{2}{3} - \frac{1}{3} \):
- Convert \( 1 \frac{2}{3} \) to an improper fraction: \( 1 \frac{2}{3} = \frac{5}{3} \)
- Now calculate: \[ A = \frac{5}{3} - \frac{1}{3} = \frac{5 - 1}{3} = \frac{4}{3} \]
B. \( A = -1 \frac{2}{3} + \frac{1}{3} \):
- Convert \( -1 \frac{2}{3} \) to an improper fraction: \( -1 \frac{2}{3} = -\frac{5}{3} \)
- Now calculate: \[ A = -\frac{5}{3} + \frac{1}{3} = -\frac{5 - 1}{3} = -\frac{4}{3} \quad \text{(not equal to } \frac{4}{3}\text{)} \]
C. \( A = \frac{15}{3} + \frac{1}{3} \):
- Now calculate: \[ A = \frac{15}{3} + \frac{1}{3} = \frac{15 + 1}{3} = \frac{16}{3} \quad \text{(not equal to } \frac{4}{3}\text{)} \]
D. \( A = 1 \frac{2}{3} + \frac{1}{3} \):
- Convert \( 1 \frac{2}{3} \) to an improper fraction: \( 1 \frac{2}{3} = \frac{5}{3} \)
- Now calculate: \[ A = \frac{5}{3} + \frac{1}{3} = \frac{5 + 1}{3} = \frac{6}{3} = 2 \quad \text{(not equal to } \frac{4}{3}\text{)} \]
Based on the evaluations, the expression that equals \( A = \frac{4}{3} \) is:
A. \( A = 1 \frac{2}{3} - \frac{1}{3} \).